PENGARUH GAYA KEPEMIMPINANDAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KOTA BATAM - Dhenny Asmarazisa (Universitas Riau Kepulauan, 2019)
Performance is the result of individual work can be accomplished in accordance with the duties and functions in the achievement of organizational goals. Leadreship style is a pattern of behavior held to affect the invidual in achieving certain goals. While organizational culture is the values held by individuals within an organization.This study aims to determine the relationship between leadership style and organizational culture as an independent variable on the performance as an independent variable. This research is descriptive quantitative research with a survey approach.The population in this study were employees at the Parlement Secretariat of Batam, the determination of the sample table 90 refers Isaac and Michael with standard error of 10%. The analytical method used is the method of multiple regression and correlation. The analysis result obtained is a style of leadership has a positive and significant impact on performance, organizational culture has a positive and significant impact on performance, and leadership styles and organizational cultures together in a positive and significant effect on performance. Keywords: Leadership Style, Organizational Culture, Performance